Efeitos de uma intervenção psicanalítica em pais de crianças com diagnóstico de transtorno do espectro autista - Tobias, Janaina Pompeu (2017)
Autistic Spectrum Disorder, in psychoanalytic metapsychology, is understood through its negativity, of which it wasn´t possible to structure the subject. The first logical time of the constitution is the Stage of the Mirror, which is possible through the external agents who fulfill the maternal and paternal functions, which in exercising their role, put in action the operations of alienation and separation. In the case of TEA there is an impossibility of alienation, the movement that fails is the incidence of the imaginary in the real, the imaginary investment of the Other in the baby is truncated. As Jerusalinsky writes(1999, p. 139): "autistic children are taken in the real of the object". And, according to Mannoni (1923/1989) the father-mother-child dynamics is put long before the baby is born, and it is fundamental to involve parents in the treatment of their children, because they resonate the unconscious conflicts of the parents. Objective: To analyze the effects of a psychoanalytic intervention with parents of children with TEA, seeking to understand and analyze the discursive position of these parents. Method: Longitudinal study of mixed character (quantitative and qualitative). Performed at the specialty outpatient clinic of a school hospital. Participants were 7 parents of children diagnosed with TEA, of both sexes. The research's outline corresponded to the pre-intervention evaluation performed through the completion of the instruments: Socio-demographic data sheet and perception of the symptomatology of TEA, evaluation Scale for infantil autism, Inventory of Symptoms of Stress for Adults of Lipp, quality of life Scale, Self-efficacy Scale and Zarit Caretaker Overload Scale. The intervention happened through a listening group, which happened in 8 meetings lasting 90 minutes. The closure of this procedure happened through the reapplication of the instruments with the parents. Results: It was obtained that 71.4% of the participants were women, with a mean age of 38 years, 85.7% married, 57.1% with complete high school and 42.9% inactive, who didn‟t work in any type of paid work. Through the nodal points analyzed, the speech of the parents was located in the discursive node stagnated in the autistic signifier, because the parents couldn´t see in their children anything beyond the symptoms, and the children were marked by the impossibility. The interventions were performed through the retrieval of the gaze for these children from discursive turns. The results on stress showed a decrease in the means of the stress phase and the physical and psychological symptoms, however, there was no statistical significance, as well as the self-efficacy scale. Regarding the quality of life, there was a significant comparison with the psychological and environmental domain. The parents, before the intervention, presented intense and slight overload after, 43% of the parents didn´t present overload. Conclusions: The whole process of searching for a diagnosis and treatment generates a demand in these parents for a specialized knowledge about childhood, but this can generate a imprisonment to the master's discourse. The Listening Group has brought the possibility of providing symbolic exits for these children through their position in the imaginary of the parents.